Comparison of affect-regulated, self-regulated, and heart-rate regulated exercise prescriptions: Protocol for a randomized controlled trial. (September 2017) - Zenko, Zachary; O'Brien, Julia D.; Berman, Catherine J.; Ariely, Dan
Abstract: Recent evidence has highlighted the potential benefits of affect- and self-regulated exercise prescriptions for the promotion of physical activity and exercise behavior (Baldwin et al., 2016; Williams et al., 2015, 2016). However, questions remain about which characteristics of the exercise prescriptions make them more effective. Objectives: This study will compare exercise prescriptions with and without choice, and with and without an emphasis on affective valence, to determine which method of intensity regulation is most effective for increasing walking behavior. Design: Parallel-groups randomized controlled trial. Methods: Insufficiently active (less than 90 min per week of moderate-intensity activity) adults will be recruited to participate in a six-week study consisting of a two-week baseline period and four-week intervention. Walking behavior will be measured objectively using consumer-based activity monitors, and based on self-reported data. Other outcome measures will include affective attitudes, variables related to intrinsic motivation, self-reported compliance, resting heart rate, and weight. Participants will be randomized to one of four walking programs that either regulate intensity based on the choice of the intensity or based on heart rate, and either have or lack an emphasis on the affective valence of exercise. Conclusions: Recruitment and onboarding has begun. Results of this randomized controlled trial are expected to be available by the middle of 2018. Highlights: A protocol for a randomized controlled trial is introduced. This study is designed to compare four different types of exercise prescriptions. Affect-, self-, and heart rate-regulated intensities will be compared. Results are expected by the middle of 2018.